1974
DOI: 10.1002/eji.1830041212
|View full text |Cite
|
Sign up to set email alerts
|

T cell‐independent development of B memory cells

Abstract: Speen cells derived from sheep red blood cell (SRBC)-primed nude mice gave a typical secondary response when challenged in vitro with SRBC in the presence of SRBC-primed T cells. The results demonstrate that B memory cells of both IgM and IgG type develop in the absence of functioning T cells. Moreover, these results indicate that O-antigen-bearing cells, reactive t o phytohemagglutinin (PHA) or concanavalin A (Con A), are not involved in the initiation of B cell triggering, but rather in the differentiation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…This confirms the suggestions of others [11,14,20] that antibody production and memory cell induction are independ ent events.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This confirms the suggestions of others [11,14,20] that antibody production and memory cell induction are independ ent events.…”
Section: Discussionsupporting
confidence: 79%
“…Hamaoka et al [16] and Okudaira and Ishizaka [21] have shown that B cells have the most critical need for adjuvant stimulus for IgE production, and that T helper cells do not require the action of the adjuvant. The induc tion of B memory cells in the absence of T cells has been demonstrated by Diamantstein and BlitsteinWillinger [11], Thus, the 13-cRA may be having a dual effect, that of an adjuvant to prime B memory cell in duction, and in some way blocking the primary anti body response. Rhodes and Oliver [23] demonstrated that retinoids are capable of affecting macrophages by decreasing the level of Fc receptors on their sur face.…”
Section: Discussionmentioning
confidence: 99%
“…These results with antigen-specific responses are in agreement with earlier studies by Diamantstein and his collaborators on the mitogenic properties of DxS [25]. They found that the mitogenic response of splenic B cells to DxS was enhanced when T cells were removed and showed that the T cells downregulating the B cell response were cyclophosphamide sensitive, T suppressor cells.…”
Section: Isupporting
confidence: 93%
“…The results of the transfer ex periments, therefore, indicate that a haptenspecific B cell population expands in nu/nu mice by immunization with alum-absorbed DNP antigens. These findings are in agree ment with the observations of Diamantstein and Blitstein-Willinger [25], who reported that spleen cells derived from sheep red cell (SRBC)-primed nude mice gave a typical secondary plaque-forming cell response when challenged in vitro with SRBC in the presence of helper T cells.…”
Section: Discussionsupporting
confidence: 82%